Examining rape culture and rape mythson facebook fanpage of billboard:the case of kesha and dr. Luke = Nghiên cứu sự bình thường hóa hiếp dâm và những hiểu nhầm khác về hiếp dâm trên fanpage facebook của Billboard: trường hợp của Kesha và Dr. Luke - Phạm, Bảo Anh (2020)
Social media has played a pivotal role in empowering the public to openly discuss sexual assault and its aftermath. This study examines rape culture and rape my thson a widely used social media site – Facebook, specifically Facebook fanpage of Billboard via the case of Kesha and Dr. Luke. Emphasis was placed on how Facebook users respond to the case, and how rape culture and rape myths are portrayed through the responses. 1000 comments under four posts around the case reported on Facebook were coded for analysis. The study finds that while the slight majority of the comments (more than a half) show support and empathy to the victim, still a significant proportion of the comments (around a third) blame the victim. Around 10 percent of the comments demonstrate a tentative, neutral stance suggesting waiting for the decision from the court. Support and empathy to the singer are shown by debunking rape jokes and rape myths, sharing personal stories, providing further information about the complexity of sexual assault, and expressing contempt for Dr. Luke. On the other hand, by blaming Kesha on making a false accusation and not conforming to traditional gender roles, victim blamers perpetuate rape culture and rape myths. The study suggests that Facebook is an feasible platform to understand the public perspectives on sexual assault, as well as assess and combat rape culture and rape myths.